South Pole CH4 data for termination - Sowers, Todd A. (IEDA: US Antarctic Program Data Center, 2019)
Abstract: The overiding goal for our collaborative project is to provide the necessary data to construct an accurate gas age scale all along the SPICE core. Downcore measurements of CH4 and other species would help to constrain the ice age - gas age difference all along the core that is a prerequisite for the construction of the gas age vs depth profile that is the backbone for all atmospheric reconstructions.